Rainbow trout (Salmo irideus) produced in Finland V. Heat penetration in canned trout products during processing - Jorma J. Laine (Agricultural and Food Science, 1968)
In the present study the heat penetration of two canned trout products was investigated. Heat penetration was measured and fh117 parameter were calculated. In the processing, a comparison with a non-rotating (10 RPM) sterilization was made. The results indicated that smoked trout in vegetable oil (can size ø 73 X 103 mm) reached fh117 in 32 minutes with a rotation of 10 RPM and in 38 minutes without rotation. The corresponding values for trout in its own juice (can size ø 73 X 64 mm) were 79 and 81.5 minutes. At the end of the processing the cooling time from + 117°C to + 30°C was 15.5 minutes for the smoked trout in vegetable oil with a rotation of 10 RPM and 19 minutes in the non-rotating sterilization. The corresponding values for the trout in its own juice were 18.5 and 26 minutes.